2021
DOI: 10.1038/s41598-021-96204-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of feeding and starvation on antioxidant defence, fatty acid composition and lipid peroxidation in reared Oncorhynchus mykiss fry

Abstract: The effects of feeding and starvation have been studied with respect to oxidative stress and enzymatic antioxidant activities in the whole body of 4 cm rainbow trout fry Oncorhynchus mykiss (Walbaum 1792). The experiment was conducted for 28 days. The selected biomarkers for the study were determined, including non-enzymic scavengers glutathione (GSH), oxidized glutathione (GSSG) and malondialdehyde (MDA) contents and a number of enzymes are known to have major antioxidant activity, such as activities of süper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 92 publications
3
4
0
1
Order By: Relevance
“…In the meantime, 20:5 n ‐3 and 22:6 n ‐3 were selectively retained in O. macrolepis . This result was in agreement with previously research, suggesting that 22:6 n ‐3 was conserved in fasted fish (Zengin et al, 2021). This indicated that n ‐3 LC‐PUFA was important for the fish because of its irreplaceable functions (Yoon et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
“…In the meantime, 20:5 n ‐3 and 22:6 n ‐3 were selectively retained in O. macrolepis . This result was in agreement with previously research, suggesting that 22:6 n ‐3 was conserved in fasted fish (Zengin et al, 2021). This indicated that n ‐3 LC‐PUFA was important for the fish because of its irreplaceable functions (Yoon et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
“…In the current study, the SOD, GSH-PX and CAT activities both in the hepatopancreas and intestines showed an increasing trend during starvation. The finding was in agreement with previous ones indicating that food scarcity could activate the antioxidant defense mechanisms of fish [ 23 ]. The degree of lipid peroxidation can be measured by the MDA concentration.…”
Section: Discussionsupporting
confidence: 93%
“…It is well-known that superoxide dismutase (SOD), glutathione peroxidase (GSH-PX) and catalase (CAT) are several important antioxidant enzymes. Antioxidant enzymes play a vital role in scavenging free radicals and regulating the generation of ROS, thereby activating the antioxidant defense mechanism and further improving the immune status in fish [ 23 ]. Previous studies reported that 14 days of starvation could elevate antioxidant enzymes activities in fish such as the Chinese perch ( Siniperca chuatsi ) (250 ± 22 g) and Stellate Sturgeon ( Acipenser stellatus ) (331.3 ± 71.8 g) [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result showed that starvation caused oxidative stress in the fish body in a chronic manner. The same studies were seen in rainbow trout ( Oncorhynchus mykiss ) ( 34 ), European sea bass ( Dicentrarchus labrax ) ( 35 ), Soleimani ( Mesopotamichthys sharpeyi ) ( 36 ), brown trout ( Salmo trutta ) ( 37 ). Persisting oxidative stress can activate a large range of transcription factors, such as NF-κB, Nrf2 and HIF-1α.…”
Section: Discussionsupporting
confidence: 61%